“An Application of J.P Gond’s “CSR-CFP Behavioural Model for Employees” to Employees at Enterprise Rent-a-Car” - Cooper, Jack (2010)
Abstract This study sets out to test Gond’s (2010) “CSR-CFP Behavioural Model for Employees”. The study interviews eight employees of Enterprise Rent-a-Car in an attempt to establish the extent to which employee perceptions are affected by an organisation’s Corporate Social Performance. Gond’s assumption that employees’ perceptions will result in employee social behaviours in the form of either Organisational Citizenship Behaviours or Organisational Irresponsible Behaviours is discussed, with the implication made that it is instead individually held values and beliefs that instruct employee actions in the workplace.